THE DIURNAL ORDER OF THE IMAGE IN DRACULA, BY BRAM STOKER - Vescia Zanini, Claudio (Organon, 2018)
The article proposes a reading of Bram Stoker’s Dracula analyzing the imagery in the novel in accordance with the Diurnal Order of the Image (DURAND, 1999), a perspective that encompasses images within three antithetical dichotomies: the theriomorphic and diæretic images (respectively related to an animal archetypology and to the devices and weapons of the hero), the nyctomorphic and spectacular images (related to darkness and light) and catamorphic and ascensional images, which are connected to falling and rising. The conclusion highlights the universality in the imagery Stoker employs in his work, which explains Dracula’s timelessness and power. KEYWORDS: Dracula; Victorian literature; diurnal order of the image; vampire fiction.